Innovative Strategies for Empowering Rural Communities: International Experiences and Applications in Afghanistan - Mazloum Yar, Fayaz Gul; Rahmani, Mullajan (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study explores innovative strategies for rural community empowerment, focusing on international best practices and their potential application in Afghanistan. Rural empowerment is critical for sustainable development, enhancing socio-economic resilience, and reducing poverty, particularly in underserved Afghan communities. However, limited research addresses context-specific approaches that integrate both global experiences and local needs. This study aims to fill this gap by identifying effective empowerment models from various countries and examining their relevance within the Afghan socio-cultural and economic landscape. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 300 rural participants across Afghanistan, along with interviews and focus group discussions with local leaders, NGO representatives, and international experts. Descriptive and inferential statistics were applied to survey data, while thematic analysis was used for qualitative insights to capture diverse perspectives on empowerment challenges and enablers. Key findings highlight that community-led vocational training, microfinance initiatives, and gender-inclusive programs are essential for effective empowerment. Notably, vocational skills aligned with local needs significantly increased economic independence, while community-managed microfinance enhanced financial security and trust. Gender-inclusive approaches were found to be vital in overcoming social barriers, particularly in conservative rural regions. The study concludes that adapting international empowerment models to local contexts can significantly improve their impact. Recommendations include establishing localized training, fostering cooperative economic activities, and introducing community-led monitoring systems. This research contributes to the field by providing a practical framework for rural empowerment in Afghanistan, offering policymakers actionable insights to design culturally sensitive, sustainable development programs.